742. Breakthrough Invasive Fungal Infections with Isavuconazonium Sulfate versus Voriconazole as Primary Antifungal Prophylaxis in Patients with Acute Myeloid Leukemia (AML) who Received Induction Chemotherapy. (31st December 2020) - Singam, Hareesh v; Pasikhova, Yanina; Quilitz, Rod; Greene, John N; Baluch, Aliyah
Abstract: Background: Fungal infections in patients with hematologic malignancies are associated with high mortality. Primary antifungal prophylaxis has been shown to be a more effective strategy than treating a documented infection. This retrospective analysis aims to compare the rates of breakthrough invasive fungal infections in patients with acute myeloid leukemia (AML) who received induction chemotherapy and were prescribed voriconazole (Vori) or isavuconazonium (Isv) for primary antifungal prophylaxis. The European Organization for Research and Treatment of Cancer/ Invasive Fungal Infection Cooperative Group and National Institute of Allergy and Infectious Diseases Mycoses Study Group criteria was used to categorize incidence of breakthrough invasive fungal infections bIFI into 'possible', 'probable' or 'definite' groups who required treatment with liposomal amphotericin B, echinocandin, and/or different triazole. Methods: This is a single-center retrospective analysis of patients who underwent induction chemotherapy for newly diagnosed AML. These patients received either Vori or Isv sulfate as the primary antifungal prophylaxis at Moffitt Cancer Center between July 2017 and June 2019. Patients who were over 18 years old and received at least 10 days of uninterrupted primary antifungal prophylaxis with either Vori or Isv sulfate were included in the study. Patients with a history of stem cell or solid organ transplant, Human Immunodeficiency Virus, relapsed AML or who received systematic antifungal, other than fluconazole, therapy within 30 days to induction chemotherapy were excluded. Results: 250 patients were screened for the study and out of which 118 patients met the above criteria. There was a 20.2% (18/89) break through rate of fungal infections in the Vori arm and 17.2% (5/29) in the Isv arm. In the Vori arm there were 15 possible bIFIs, 3 probable bIFIs and 0 definite bIFIs. In the Isv arm there are 2 possible bIFIs, 2 probable bIFIs and 1 definite bIFIs. Conclusion: There is no significant statistical difference (Using the Fisher Exact test statistic p=1) between the Isv and Vori in patients who received these agents for primary fungal prophylaxis for induction chemotherapy for AML at Moffitt Cancer Center between July 2017 - June 2019. Disclosures: Rod Quilitz, Pharm D., Astellas (Advisor or Review Panel member)